Critical Analysis of Ganjar’s Speech Covid-19: A Constructed Political Identity - Prayudisti Shinta Pandanwangi; Nurhayati Nurhayati; Zuly Qodir (Langkawi: Journal of The Association for Arabic and English, 2020)
This paper examines Ganjar Pranowo’s political identity through his linguistic features constructed through his speech for responding the case of some of Ungaran citizen’s refusal on accepting a Covid-19 patient’s remain body. The speech is analyzed with Fairclough’s CDA as the main framework of analysis. There are three dialectical stages to complete his framework, namely the text analysis, the interpretation of text analysis, and the explanation. The textual part of the analysis will be explained by using Halliday’s systemic functional linguistics. Meanwhile, the interpretation part will be examined by using Halliday’s appraisal system, and van Dijk’s political discourse analysis will analyze the explanation part. This article states that the interpretation analysis are both ‘judgement’ and ‘appreciation’ from Ganjar shows some degrees of positive polarity and other degrees of opposing polarity. The Ganjar’s political identity represented from his response-speech is humanitarian-oriented, socio-religiously aware, status quo holder, and as a part of the bigger political system’s discourse maker. In this case, response-speech could be selected and in line with the context of society need. Therefore, this article suggests that disaster management should not differentiate community identity on the one hand. The elite also could deliver the policies in a soft statement that is accepted by the public on the other hand.